The impact of police 'process-driven responses' on supporting lesbian, gay, bisexual and/or transgender + victim-survivors of domestic abuse in England - Butterby, Kate (Journal of family violence, 2024)
Purpose: The public story of domestic abuse (DA) sets out DA as a problem of cisgender, heterosexual ‘strong’ men, perpetrating physical abuse towards cisgender, heterosexual ‘weak’ women. Drawing upon this narrative, LGB and/or T + victim-survivors may not see their experiences reflected, and similarly, practitioners may view abuse in LGB and/or T + people’s relationships as less serious, as ‘mutual’ or may miss dynamics unique to DA within these relationships. This article argues that when assessing risk and making subsequent decisions in relation to abuse within LBG and/or T + people’s relationships, police enact ‘process-driven responses’, meaning that the same procedures are followed for all DA cases irrespective of the different identities and/or needs of the victim-survivors. We explore how process-driven responses are underpinned by the public story, and how this impacts the services provided to LGB and/or T + victim-survivors. Methods: Semi-structured qualitative interviews (n = 35) with police officers, police staff, support practitioners and victim-survivors were undertaken and analysed thematically. Results: Findings suggest that by enacting process-driven responses, police feel that they are providing an equitable service to all victim-survivors. However, these responses draw heavily on the public story of DA, focusing primarily on cisgender, heterosexual stereotypes and the presence of physical injuries. Conclusions: Treating everyone the same’ can leave experiences of LGB and/or T + victim-survivors invisible, minimised and not understood. This has implications in relation to inadequate responses being provided, such as victim-survivors being arrested, mutual blame being ascribed and lack of police knowledge in relation to appropriate support provision. Suggestions for policy and practice will follow.